Cardiac cephalalgia: A deadly case report - Santos, Paulo Sergio Faro; Pedro, Matheus Kahakura Franco; Andrade, Ana Carolina (Headache Medicine, 2019)
Cardiac cephalalgia is a nosologic entity that has only been acknowledged by the turn of the century, and is, consequently, often underdiagnosed, even by experienced neurologists. Unlike most headaches, however, failing to provide a proper and timely diagnosis can have deadly consequences. Report of a case of cardiac headache attended at the emergency department and literature review. This entity was first described in 1997; no studies have yet determined its prevalence, with the literature relying on case reports. The pathophysiology remains a mystery, with three main hypothesis: spinal convergence of cardiac visceral afferent nerves with somatic afferent nerves from the head, increase of intracranial pressure from decrease in cerebral venous return originated from the reduced cardiac output, and release of inflammatory markers during cardiac ischaemia, such as bradykinin, serotonin and histamin, causing vascular changes. Distinguishing this pathology from others, especially migraine, with which it shares many traits, is of paramount importance: vasoconstrictor drugs such as triptans are absolutely contraindicated, and the outcome can be dramatic. This case illustrates the need to promptly recognize this rare entity since failure to diagnose it can have devastating consequences.